2015
DOI: 10.1177/1535370215606814
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting myostatin signaling prevents femoral trabecular bone loss and microarchitecture deterioration in diet-induced obese rats

Abstract: Besides resulting in a dramatic increase in skeletal muscle mass, myostatin (MSTN) deficiency has a positive effect on bone formation. However, the issue about whether blocking MSTN can inhibit obesity-induced bone loss has not been previously investigated. In the present study, we have evaluated the effects of MSTN blocking on bone quality in high-fat (HF), diet-induced obese rats using a prepared polyclonal antibody for MSTN (MsAb). Twenty-four rats were randomly assigned to the Control, HF and HF þ MsAb gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…3A), in line with prior reports that myostatin suppression leads to reduced serum TNFα level [41]. Bone marrow expression of GADD45, the gene for growth arrest and DNA damage repair and also a downstream target of TGFβ signaling [42], was lower in the ActRIIB.Fc-treated group as compared to the control group (Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…3A), in line with prior reports that myostatin suppression leads to reduced serum TNFα level [41]. Bone marrow expression of GADD45, the gene for growth arrest and DNA damage repair and also a downstream target of TGFβ signaling [42], was lower in the ActRIIB.Fc-treated group as compared to the control group (Fig.…”
Section: Resultssupporting
confidence: 89%
“…This effect was associated with reduced bone marrow expression of TNFα, GADD45 and SOST in the SIV-infected monkeys. This observation is in agreement with previous reports that these genes are mutually inducible and subject to induction during chronic inflammatory diseases and by myostatin per se [41,47,52]. Importantly, treatment with ActRIIB.Fc results in continuous bone growth without affecting serum testosterone levels, suggesting that its bone effect occurs independently or downstream of testosterone, consistent with a previous report that ActRIIB.Fc reverses bone loss induced by androgen-deprivation in rodents [28].…”
Section: Discussionsupporting
confidence: 93%
“…The role of MSTN in muscle growth regulation and the disruption of its gene have been demonstrated to cause muscle hypertrophy and increase bone mass. Our previous work showed that blocking MSTN with a polyclonal anti-MSTN antibody preparation improves the trabecular bone microstructure (42), suggesting that therapeutic modulation of MSTN in vivo may be an effective strategy for preserving muscle mass and bone metabolism with diabetes. In the present study, weight-bearing running significantly inhibited STZ-induced MSTN expression, indicating that the inhibition of MSTN may alleviate STZ-induced diabetic muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…9 TNF-α stimulation enhanced the myostatin expression via the NF-κB pathway. 18 Thus, myostatin likely interacts with inflammatory cytokines and contributes to the presence and progression of OA. 16 TNF-α can activate myostatin through the NF-κB pathway in myotubes, 17 but inhibition of the NF-κB pathway can inactivate myostatin.…”
Section: Discussionmentioning
confidence: 99%
“…17 Moreover, silencing myostatin with myostatin antibody decreases TNF-α and IL-6 levels. 18 Thus, myostatin likely interacts with inflammatory cytokines and contributes to the presence and progression of OA.…”
Section: Discussionmentioning
confidence: 99%